2020
DOI: 10.5194/egusphere-egu2020-672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can combined application of biochar and nitrogen promote microbial functions and root plasticity for plant growth in low-fertile soils?

Abstract: <p>Biochar and nitrogen (N) fertilizers are frequently applied to improve soil properties and increase crop productivity. However, it remains unclear how root plasticity, soil enzyme activities, N and (phosphorus) P cycling in plant-soil system are changed after application of biochar, N or their combination. To address these questions, left and right parts of rhizoboxes were filled with silty-clay loam subsoil amended with biochar (15 g kg<sup>-1</sup> so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, the increased SAN pool in WSP-amended soil could potentially be interpreted as lower N leaching or higher N immobilization (Oladele et al, 2019), in which soil enzyme plays an important role (Gao and Deluca, 2018). For instance, Song et al (2020) pointed out that wheat-straw biochar boosted the activities of bglucosidase and leucine aminopeptidase in maize rhizosphere soil, and Gao and Deluca (2020) found that wood-based biochar improved the relative abundance of bacterial amoA gene in the rangeland ecosystem, which contributed to the immobilization of N. Moreover, these superior properties of biochar regarding porosity and specific surface area could enhance nutrient transport through diffusion and/or mass flow (Oladele et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increased SAN pool in WSP-amended soil could potentially be interpreted as lower N leaching or higher N immobilization (Oladele et al, 2019), in which soil enzyme plays an important role (Gao and Deluca, 2018). For instance, Song et al (2020) pointed out that wheat-straw biochar boosted the activities of bglucosidase and leucine aminopeptidase in maize rhizosphere soil, and Gao and Deluca (2020) found that wood-based biochar improved the relative abundance of bacterial amoA gene in the rangeland ecosystem, which contributed to the immobilization of N. Moreover, these superior properties of biochar regarding porosity and specific surface area could enhance nutrient transport through diffusion and/or mass flow (Oladele et al, 2019).…”
Section: Discussionmentioning
confidence: 99%